Love rules : silent Hollywood and the rise of the managerial class - Cooper, Mark Garrett (Minneapolis : University of Minnesota Press, 2003)
Through close study of such films as Birth of a Nation, Enoch Arden, The Crowd, Why Change Your Wife? and The Jazz Singer, Mark Garrett Cooper uncovers an intimate connection between Hollywood romances of the silent era and the empowerment of a managerial class.
The visual love story -- The public -- The influence industry -- Ethnic management.
Includes bibliographical references (pages 217-267) and index.
Print version record.
English.
JSTOR
Keywords: Love in motion pictures; Silent films -- United States -- History and criticism; Motion picture audiences; Race relations in motion pictures; Amour au cinéma.; Films muets -- États-Unis -- Histoire et critique; Cinéma -- Publics; Relations raciales au cinéma.; PERFORMING ARTS -- Film & Video -- Reference; PERFORMING ARTS -- Film & Video -- General; Love in motion pictures; Motion picture audiences; Race relations in motion pictures; Silent films; United States; Electronic book; Criticism, interpretation, etc